Observar la innovación educativa en Europa - Botrel, Jean-François (Revista Española de Pedagogía, 2018)
As a result of an initiative of the INRP, an European Observatory for educational innovation has been set up. Its main goals are related to research and training in the field of educational innovations throughout Europe. The Observatory wishes to operate as an open data base of innovation and change in European education systems. Thus, it is mainly addressed to researchers in the field, especially those interested in the comparative study of educational policies. Up to the present, five different issues have concentrated the Observatory's efforts: equality of educational opportunity, teaching and learning foreign languages, new profiles for teaching, teacher training, and headmasters' training
Keywords: innovación educativa; Europa; Revista Española de Pedagogía